Interventions for Physician Burnout: A Systematic Review of Systematic Reviews - Kalani, Simin Dokht (Int J Prev Med, 2018)
Occupational burnout is a common syndrome among physicians, and several individual-directed and organization-directed interventions have been implemented to reduce it. Until now, several review studies have tried to identify and introduce the most appropriate interventions. The aim of this article was to systematically review systematic review studies of interventions for physician burnout to evaluate and summarize their results, and ultimately guide researchers to select appropriate interventions. A search was conducted to find review studies and systematic reviews in Cochrane Database of Systematic Reviews, Medline, Google Scholar, PubMed, and PsycINFO. Two reviewers independently selected and evaluated the studies based on inclusion criteria. Four of seven obtained review studies and systematic reviews met the inclusion criteria. These studies have reviewed individual-directed and organization-directed interventions intended to reduce burnout among medical students, interns, physicians, residents, and fellows. Various studies of the effectiveness of individual- and organization-directed interventions have obtained different results. This research has shown that reaching conclusions about effective interventions (individual- or organization-directed) for physician burnout is not easy and that a number of mediating or moderating variables probably influence the effectiveness of these interventions. Therefore, it is necessary to understand approaches and interventions for the prevention or reduction of physician burnout to fill the gaps in research. In addition, review studies are required to be more precise in choosing their criteria to find more accurate results.